Full Employment at Whatever Cost - Viner, Jacob (Quarterly Journal of Economics, 1950)
I. Deficiency of "effective demand" as cause of unemployment, 385. — II. Full employment and inflation, 388. — III. Full employment and economic and political institutions, 392. — IV. Domestic measures to prevent unemployment, 393. — V. International disequilibrium, 396. — VI. Harmonization of foreign trade targets, 400. — VII. Stabilization of international investment, 401. — VIII. Stabilization of international trade, 404. — IX. Final comments, 407.